BCH-2763, a Novel Potent Parenteral Thrombin Inhibitor, Is an Effective Antithrombotic Agent in Rodent Models of Arterial and Venous Thrombosis – Comparisons with Heparin, r-Hirudin, Hirulog, Inogatran and Argatroban - Finkle, Carolyn D.; Pierre, Annie St.; Leblond, Lorraine; Deschenes, Isabelle; DiMaio, John; Winocour, Peter D. (Thrombosis and Haemostasis, 1998)
Current clinical use of heparin as an antithrombotic agent is limited by suboptimal efficacy and safety considerations. Thrombin’s central role in thrombosis makes it an attractive target to develop more effective and safer antithrombotic agents. BCH-2763 is a novel, potent (Ki: 0.11 nM), low molecular weight (1.51 kDa), bivalent direct thrombin inhibitor. The antithrombotic efficacy of BCH-2763 in vivo following i.v. bolus plus infusion in rats was compared in arterial and venous thrombosis models with two other bivalent direct thrombin inhibitors, r-hirudin and hirulog, with two catalytic site-directed thrombin inhibitors, inogatran and argatroban, and with heparin. In vivo efficacy was related to inhibition in vitro of fibrin clot formation, thrombin-induced aggregation of rat or human washed platelets and activity of free and plasma clot-bound thrombin. All the direct thrombin inhibitors were effective on both arterial and venous thrombosis at markedly lower fold aPTT increases than heparin. The antithrombotic doses of all inhibitors against venous thrombosis were less than against arterial thrombosis. The rank order of potency based on doses (mg/kg/h) required for full efficacy against arterial thrombosis was BCH-2763 (1.2) inogatran (1.5) r-hirudin (1.8) hirulog (3.3) argatroban ( 3.0); heparin required a markedly higher dose (5.7). In venous thrombosis the doses required for full efficacy were substantially lower for the bivalent (BCH-2763: 0.12; r-hirudin: 0.12; hirulog: 0.18) than for the catalytic site-directed (inogatran: 0.48; argatroban: 0.90) thrombin inhibitors; the dose required for heparin was 0.19. All the direct thrombin inhibitors caused similar shifts in aPTT at doses required to inhibit arterial thrombosis, but BCH-2763 inhibited venous thrombosis at lower aPTT fold increases. In vivo antithrombotic efficacy of direct thrombin inhibitors correlated with their inhibitory activity in vitro against fibrin clot formation and platelet aggregation. In contrast to heparin, all the direct thrombin inhibitors inhibited plasma clot-bound thrombin, but the relative IC50s did not correlate with their antithrombotic efficacy. In summary, direct thrombin inhibitors are more effective than heparin in inhibiting arterial and venous thrombosis in rats with less aPTT increases. BCH-2763 is effective at lower doses than the other direct thrombin inhibitors and for venous thrombosis at a smaller aPTT increase. BCH-2763 may offer an improved therapeutic index in the treatment of thromboembolic complications over heparin and other direct thrombin inhibitors.